Pre- and Postictal Changes in the Innate Immune System: Cause or Effect? - Lang, Johannes; Olmes, David G.; Proske, Manuel; Hagge, Mareike; Dogan Onugoren, Mujgan; Rothhammer, Veit; Schwab, Stefan; Hamer, Hajo (European neurology, 2021)
Introduction: Recent studies have shown that inflammatory processes might play a role in epileptogenesis. Their role in ictogenesis is much less clear. The aim of this study was to investigate peri-ictal changes of the innate immune system by analyzing changes of immune cells, as well as pro- and anti-inflammatory cytokines. Methods: Patients with active epilepsy admitted for video-EEG monitoring for presurgical evaluation were included. Blood was sampled every 20 min for 5 h on 3 consecutive days until a seizure occurred. After a seizure, additional samples were drawn immediately, as well as 1 and 24 h later. To analyze the different populations of peripheral blood mononuclear cells, all samples underwent FACS for CD3, CD4, CD8, CD56, CD14, CD16, and CD19. For cytokine analysis, we used a custom bead-based multiplex immunoassay for IFN-gamma, IL-1 beta, IL-1RA, IL-4, IL-6, IL-10, IL-12, IL-17, MCP-1, MIP-1 alpha, and TNF alpha. Results: Fourteen patients with focal seizures during the sampling period were included. Natural killer (NK) cells showed a negative correlation (rho = -0.3362, p = 0.0195) before seizure onset and an immediate increase to 1.95-fold afterward. T helper (T-H) and B cells decreased by 2 and 8%, respectively, in the immediate postictal interval. Nonclassical and intermediate monocytes decreased not until 1 day after the seizures, and cytotoxic T (T-C) cells showed a long-lasting postictal increase by 4%. IL-10 and MCP-1 increased significantly after seizures, and IL-12 decreased in the postictal phase. Discussion/Conclusion: Our study argues for a role of the innate immune system in the pre- and postictal phases. NK cells might be involved in preictal changes or be altered as an epiphenomenon in the immediate preictal interval.
CRIS-Team WoS Importer:2021-07-09